Implementation of Syibhul Iddah in KUA Klojen District: A Study Based on the Circular Letter of the Ministry of Religious Affairs - Putri, Ramadhani Islam; Suhadak, Faridatus (Sakina: Journal of Family Studies, 2025)
Iddah is a waiting period given to women to check whether they are pregnant or not. Until the issuance of the Circular Letter from the Director General of Islamic Community Guidance, Ministry of Religious Affairs No: P-005/DJ.III/Hk.00.7/10/2021, which regulates the application of the waiting period (Syibhul Iddah) for men who have divorced before remarrying. This research aims to describe the implementation of Syibhul Iddah based on the Circular Letter at the KUA Klojen District and to analyze its concept from the perspective of Wahbah Az-Zuhaili. This research uses a juridical-empirical approach with a qualitative descriptive method. Data sources were obtained from primary sources in the form of interviews with informants such as the Head of KUA, modin, and widowed prospective grooms, and were supported by secondary sources such as relevant literature, including the Islamic book "Wa Adilatuhu" and Circular Letters. Data were collected through interviews and documentation. The research results show that the KUA of Klojen District has implemented this policy in accordance with the regulations. The KUA does not process the administration of male prospective brides who are still in the iddah period of their former wives. This policy provides benefits, particularly in protecting women's rights post-divorce. Furthermore, an analysis from the perspective of Wahbah Az-Zuhaili shows that Syibhul Iddah aligns with two shari'ah prohibitions, namely the prohibition of marrying more than four wives (including in the case of raj'i divorce) and the prohibition of marrying women who are blood relatives of former wives.